ANALYSIS OF FINANCIAL PERFORMANCE USING FINANCIAL RATIO ACCORDING TO THE DECREE OF THE MINISTER OF BUMN NUMBER KEP-100/MBU/2002 - Jufri Sani Akbar; Muhammad Ikhsan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research aims to determine the level of financial performance of State-Owned Enterprises using financial ratios according to the Decree of the Minister of BUMN No: KEP-100/MBU/2002. The BUMN that is the object of research is PT. Timah Tbk. The data source used is secondary data contained in the Indonesian Stock Exchange by taking data samples using purposive sampling taking into account the data which is still updated and published on the Indonesian Stock Exchange. while the data analysis technique uses quantitative analysis with a financial ratio approach contained in the Decree of the Minister of BUMN No: KEP-100/MBU/2002. The results of this research show that the company's financial performance in 2019 received the predicate B which means unhealthy, in 2020 the company's financial performance received the predicate BB which means unhealthy, in 2021 the company's financial performance received the predicate AA which means healthy, in 2022 the company's financial performance received the predicate AA means healthy, while in 2023 the company's performance will receive the title BB, which means unhealthy. Keywords: Financial Performance and Financial Ratios